Impacts of cropping systems on soil health and microbial ecology - Akley, Korbla Edwin (Kansas State University, 2015)
Declining soil health is the underlying cause of decreasing agricultural productivity and environmental degradation. To address this challenge, research was conducted to determine how: (1) cover crops affect soil health in Kansas, USA and (2) direct seeding mulch–based cropping (DMC) systems affect soil health in Nyankpala, Ghana. Soil health indicators assessed include: biomass yield (kg ha[superscript]-1), soil microbial respiration (SMR), soil microbial C and N (MBC & MBN), potentially mineralizable N (PMN), dissolved organic carbon (DOC), soil organic C (SOC), soil total nitrogen (TN), phospholipid fatty acid analysis (PLFA), water stable aggregate (WSA), bulk density, pH, N, P, K, Ca and Mg. DMC systems from Ghana yielded significantly greater biomass compared to the control. High biomass produced by DMC systems did not increase SOC and PMN relative to the control. Fertilizer application had a significant impact on biomass production, which resulted in a significant increase in SOC and PMN in the 0-5 cm soil layer. Soil pH was significantly reduced by cropping systems and fertilizer in the 0-5 cm soil layer. Microbial biomass N, TN, SMR, N, P, Ca and Mg were not affected by the DMC cropping systems. Application of mineral fertilizer increased SMR, MBN, TN, N, and P. Soil K was also significantly affected by cropping systems and mineral fertilizer. The combination of mineral fertilizer and plant residues would be needed to improve soil health and increase crop productivity in the Guinea Savanna Zone of Ghana. Liming would be required to address low soil pH. In the USA, of all the soil health indicators examined, actinomycetes, gram-positive bacteria, fungi-bacteria ratio (F:B), SMR, MBN and WSA, were those significantly influenced by cover crops. The interactive effect of cover cops and N fertilizer also affected gram-positive bacteria, total PLFA, MBN, F:B ratio and WSA. Cover crop residues contributed to the observed differences in these indicators. The low response of soil health indicators suggest further evaluations are needed to determine the effectiveness of the indicators.
Keywords: Soil Health; Soil Microbial Ecology; Cropping Systems; Cover Crops; Agronomy (0285); Soil Sciences (0481)